Auditory and Phonetic Processes in Speech Perception - Wright, Richard; Tucker, Benjamin V. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the past two decades, great advancements have been made in phonetic, auditory, and psycholinguistic research on speech perception. As the fields have advanced, there has been increasing interdisciplinary collaboration between them, which has, in turn, revealed their interdependence. The aim of this Special Issue is to bring together top scholars in these three related areas to present research in a single volume with papers ranging from the neurophysiology of hearing, to phonetic and linguistic factors, to factors related to hearing loss and assistive devices, second language learning and accentedness, and the processing of speech and the mental lexicon. We invite you all to read the high-quality papers in this Special Issue.